Factors Affecting Nutritional Status of Children with Down Syndrome of 7 to 12 Year-Old in Medan - Reynard Andrew; Nenni Dwi Aprianti Lubis; Fitriyani Nasution; Deryne Anggia Paramita (Masters Program in Public Health, 2023)
Background: Despite the increasing prevalence of overnutrition, the increasing number of children with Down syndrome, followed by the higher risk of children with Down syndrome to experience overnutrition, research conducted on factors that influence the nutritional status of children with Down syndrome is still limited in Indonesia. This research was conducted to look at the comparison of factors affecting the nutritional status of children with Down syndrome in the 7-12-year-old age group in Medan.Subjects dan Method: This research is an analytical cross-sectional study design. This research was conducted by distributing questionnaires to mothers of children with Down syndrome at POTADS Medan. The sampling method used is purposive sampling and data that meets the inclusion and exclusion criteria is selected. The number of samples were 30 children with Down syndrome. The data is then analyzed with Spearman’s correlation using SPSS with children’s nutritional status as the dependent factor and paternal education, maternal education, total parents’ earnings, children's energy intake, children’s diet quality, children’s physical activity, and maternal nutritional knowledge as the independent factors.Results: Correlations were found between the nutritional status of the children and paternal education (p= 0.019; r= -0.42), between children’s nutritional status and children's energy intake (p= 0.002; r= 0.55), and between children’s nutritional status and children’s diet quality (p= 0.015; r= -0.44) with confidence interval at 95%.Conclusion: Strong negative correlation against children’s nutritional status was found in paternal education and children's diet quality, while strong positive correlation was found in children’s energy intake. Indirect correlations against nutritional status were found in maternal education, parents’ total income, and maternal nutritional knowledge score. Keywords: down syndrome, diet quality, bmi. Correspondence: Reynard Andrew. Universitas Sumatera Utara, Jalan Dr. T. Mansur No.9, Padang Bulan, Kec. Medan Baru, Kota Medan, Sumatera Utara 20222, Indonesia. Email: reydrew7@gmail.com. Mobile: +6285361991111.